Clot permeability and histopathology: is a clot's perviousness on CT imaging correlated with its histologic composition?. (25th June 2019) - Benson, John Charles; Fitzgerald, Sean T; Kadirvel, Ramanathan; Johnson, Collin; Dai, Daying; Karen, Doyle; Kallmes, David F; Brinjikji, Waleed
Abstract : Background: Clot perviousness in large vessel occlusion has been shown to be associated with improved recanalization outcomes with mechanical thrombectomy and intravenous thrombolysis. Objective: To evaluate the association between clot perviousness based on thrombus attenuation increase (TAI) on CT, and histologic composition of clots in acute ischemic stroke (AIS). Methods: A retrospective review was completed of patients with AIS secondary to large vessel occlusion, non-contrast CT (NCCT) and CT angiography (CTA) images, and histologic analysis of the retrieved clot. TAI was measured by subtracting clot attenuation on NCCT from the attenuation on CTA. Up to 3 regions of interest (ROIs) were evaluated on each clot; the average attenuation was used for analysis if multiple ROIs were assessed. Pervious clots were defined as TAI ≥10 Hounsfield units (HUs); impervious clots had TAI <10 HU. Histopathologic analyses of clots were assessed for relative compositions of red blood cells (RBCs), white blood cells (WBCs), fibrin, and platelets/other. Results: 57 patients were included. Pervious clots were more likely to be RBC rich (p=0.04); impervious clots were more likely to be fibrin and WBC rich (p=0.01 for both). Pervious clots also had greater RBC density than impervious clots (49.8% and 33.0%, respectively; p=0.006); fibrin density of pervious clots was lower than that of impervious clots (17.8% and 23.2%, respectively; p=0.02). Conclusion: Clot perviousness, assessed on NCCT and CTA imaging, is associated with higher RBC density and lower fibrin density, offering a possible explanation for the higher rates of successful thrombectomy and favorable clinical outcome seen in such patients.